Welcome to our community

Be a part of something great, join today!

series multiplication

Lisa91

New member
Jan 15, 2013
29
I multiplied two series $\displaystyle \sum_{n=1}^{\infty} (-1)^{n} \frac{1}{n^{\frac{3}{4}}}$ and $\displaystyle \sum_{n=1}^{\infty} (-1)^{n} \frac{1}{n^{\frac{1}{4}}}$. I got $\displaystyle 1 + \frac{1}{2^{\frac{3}{4}}2^{\frac{1}{4}}}+\cdots$ I don't know how to write it with symbols so that I could investigate whether it's convergent or not. I'd be thankful for your help!
 
Last edited by a moderator:

Sherlock

Member
Jan 28, 2012
59
I multiplied two series $\displaystyle \sum_{n=1}^{\infty} (-1)^{n} \frac{1}{n^{\frac{3}{4}}}$ and $\displaystyle \sum_{n=1}^{\infty} (-1)^{n} \frac{1}{n^{\frac{1}{4}}}$. I got $\displaystyle 1 + \frac{1}{2^{\frac{3}{4}}2^{\frac{1}{4}}}+\cdots$ I don't know how to write it with symbols so that I could investigate whether it's convergent or not. I'd be thankful for your help!
Welcome. :] I fixed your latex. I hope the following is what you were after. Using the product formula...


$\begin{aligned} \bigg(\sum_{n=0}^{\infty} (-1)^n n^{-3/4}\bigg) \bigg(\sum_{n=0}^{\infty} (-1)^n n^{-1/4}\bigg) = \sum_{n=0}^{\infty}\sum_{k=0}^{n}(-1)^k k^{-3/4}(-1)^{n-k}(n-k)^{-1/4} = \sum_{n=0}^{\infty}\sum_{k=0}^{n}(-1)^n k^{-3/4}(n-k)^{-1/4}\end{aligned}$
 

Lisa91

New member
Jan 15, 2013
29
First of all, may I write it like this [tex] \sum_{n=0}^{\infty}(-1)^{n}\sum_{k=0}^{n} k^{-3/4}(n-k)^{-1/4} [/tex]?
[tex]\sum_{k=0}^{n} k^{-3/4}(n-k)^{-1/4}[/tex] I read that if I want to investigate whether the whole series is convergent or not I have to investigate this guy at first.
I think I could compare this guy with something that I know but I am a bit confused about 'n' and 'k'. Should I care about 'n' in this one. May I assume that it's fixed?

Then I'll investigate: [tex] \sum_{n=0}^{\infty}(-1)^{n}\sum_{k=0}^{n} k^{-3/4}(n-k)^{-1/4} [/tex]. I could apply the Leibniz formula but once again what about 'n' and 'k'.
 

Opalg

MHB Oldtimer
Staff member
Feb 7, 2012
2,702
First of all, may I write it like this [tex] \sum_{n=0}^{\infty}(-1)^{n}\sum_{k=0}^{n} k^{-3/4}(n-k)^{-1/4} [/tex]?
[tex]\sum_{k=0}^{n} k^{-3/4}(n-k)^{-1/4}[/tex] I read that if I want to investigate whether the whole series is convergent or not I have to investigate this guy at first.
I think I could compare this guy with something that I know but I am a bit confused about 'n' and 'k'. Should I care about 'n' in this one. May I assume that it's fixed?

Then I'll investigate: [tex] \sum_{n=0}^{\infty}(-1)^{n}\sum_{k=0}^{n} k^{-3/4}(n-k)^{-1/4} [/tex]. I could apply the Leibniz formula but once again what about 'n' and 'k'.
For $x$ in the interval $0\leqslant x\leqslant 1$, the function $f(x) = x^{3/4}(1-x)^{1/4}$ has a maximum value $3^{3/4}/4$ (which occurs when $x=3/4$). Putting $x=k/n$, you see that $k^{3/4}(n-k)^{1/4} \leqslant 3^{3/4}n/4$. Therefore $\displaystyle\sum_{k=0}^{n} k^{-3/4}(n-k)^{-1/4} \geqslant \frac{4(n+1)}{3^{3/4}n}>1$.